(untitled) (Bangladesh Journal of Botany, 2015)
Significant differences (p ? 0.05) were observed among the cherry tomato lines for the principal antioxidants, viz. total carotenoids, lycopene and vitamin-C. Vitamin-C content ranged from 17.62 - 46.16 mg/100 g, the total carotenoid content ranged from 3.86 - 6.66 mg/100 g and lycopene content ranged from 2.83 - 5.26 mg/100 g on fresh weight basis. The total phenolics, another important class of antioxidants, also differed significantly amongst the cherry tomato line (12.41-31.17 mg gallic acid equivalent/100 g). Significant variation (p ? 0.05) was also observed for pH and titrable acidity. The pH varied from 4.15 - 4.52 and anhydrous citric acid ranged from 0.050 up to 0.323%. The total soluble solids were 3.41 - 5.16%. The maximum vitamin-C content was recorded in VRCT-6 (46.16 mg/100 g) closely followed by VRCT-7 (45.51 mg/100 g) and VRCT-15 (44.71 mg/100 g), whereas maximum total carotenoid content were recorded in VRCT-16 (6.66 mg/100 g) followed by VRCT-7 (6.48 mg/100 g) and VRCT-1(6.36 mg/100 g), respectively. On the other hand, maximum lycopene content was estimated in VRCT-16 (5.26 mg/100 g) followed by VRCT-3 (5.23 mg/100 g) and VRCT-14 (4.73 mg/100 g). Maximum acidity and total water soluble solids were recorded in VRCT-9 (0.323%) and VRCT-7 (5.16%), respectively. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21591 Bangladesh J. Bot. 43(3): 255-260, 2014 (December)